Analisis Sifat Fisikokimia Marshmallow dengan Penambahan Royal Jelly Lebah Apis mellifera - Rika Sebtiana; Wulan Kartika Sari; Tris Harni Pebriani (Jurnal Kesehatan Qamarul Huda, 2024)
Royal jelly is a product of the cephalic gland secretion of Apis mellifera bees and is yellowish white, sour in taste, thick, and has a slight phenolic odor. Phenol is found in many foods because it can affect oxidative stability and microbiological safety so that it can function as a natural antioxidant and antimicrobial. Royal jelly is widely used to maintain stamina, cure diseases, and make cosmetics. Based on the various chemical contents and benefits of royal jelly, further research on royal jelly as a food product that has health benefits for all ages has a great opportunity to be developed. The aim of this research is to analyze the physicochemical properties of marshmallows with the addition of royal jelly from Apis mellifera bees. This research procedure consists of several stages. These stages include making marshmallow soft candy with the addition of royal jelly, analyzing the physical properties of soft candy through organoleptic tests, and hedonic tests based on panelists' assessments of color, aroma, taste, and texture. The research continued with chemical analysis through proximate tests of water, ash, protein, and carbohydrate content in the resulting marshmallow soft candy. Based on the hedonic test, marshmallow soft candy added to royal jelly has a pale yellow color, a sour taste, and smells typical of royal jelly. The addition of royal jelly to marshmallow soft candy preparations with concentrations of 25%, 50%, and 75% can increase the water content, ash content, and protein content, as well as reduce the carbohydrate content in the preparation.